Optimization Design of Mixing of Biochips Using Microfluidic - Pinaki Satpathy, Dr. Mayank Mathur (Mathematical Statistician and Engineering Applications, 2021)
Laboratory techniques in molecular biology are being revolutionized by microfluidics-based biochips, which are bringing information technology, biochemistry, and nanoelectronics together in new ways. The recent advent of biochip technology has led to a paradigm shift in various healthcare-related application sectors, such as point-of-care clinical diagnostics, high-throughput sequencing, and proteomics. Digital microfluidic-based biochips might be used to control nanoliter-volume fluid droplets on a two-dimensional electrode array. A reconfigurable microfluidic device, a mapping of different mixing techniques to synthesis tools, control software, an optimized schedule of bioassay operations, the binding of assay operations to functional units, and the layout and droplet flow-paths for the biochip will all be covered in this paper. Automated design and simplicity of use become increasingly critical as microfluidic lab-on-chips develop into multipurpose devices with smart reconfiguration and adaptability capabilities. Biochip design automation is explored in depth in this study. An overview of prominent optimization approaches and some heuristic algorithms for solving various optimization issues is given at the beginning.